Social support across eating disorder diagnostic groups: Results from the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III). (January 2023) - Kim, Sharon; Smith, Kathryn; Udo, Tomoko; Mason, Tyler
Abstract: Introduction: Previous studies have suggested the positive influence of social support on the treatment and recovery of eating disorders (EDs). Yet, more research is needed on how objective and subjective social support differ between ED diagnostic groups using nationally representative data. Therefore, the current secondary data analysis examined associations between EDs and objective and subjective social support using data from the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III) study. Methods: Participants completed measures of lifetime and past year diagnostic criteria for anorexia nervosa (AN), bulimia nervosa (BN), and binge-eating disorder (BED) and items assessing objective social support (i.e., number of close friends and close relatives) and subjective social support (i.e., perceptions of availability of support). Results: Compared to those without EDs, those with AN, BN, and BED had poorer subjective social support—or lower perceptions of social support. However, there were fewer differences regarding objective social support. Individuals with BN reported a lower number of close relatives compared to those without EDs and those with AN, but there were no differences in the number of close friends between ED groups. Those who experienced remission from EDs had higher perceptions of social support compared to those with past year EDs. Discussion: The findings show deficits in subjective social support across EDs but only lower objective social support in BN. This highlights the clinical utility of increasing perceptions of social support across EDs. The findings also show the importance of perceived social support in recovery from EDs. Highlights: We examined associations between objective and subjective social support and eating disorders (EDs). Those with lifetime EDs had lower perceptions of social support. Adults with lifetime bulimia nervosa had a lower number of close relatives. Adults remitted from EDs had higher perceived social support compared to those with past year EDs.